Novel Fitc-Labeled Igy Antibody: Fluorescence Imaging Toxoplasma Gondii In Vitro - Sert, Mehtap; Koc, Rabia Cakir; Kilinc, Yasemin Budama (NATURE PORTFOLIO, 2017)
Toxoplasmosis is caused by T. gondii and can create serious health problems in humans and also worldwide economic harm. Because of the clinical and veterinary importance of toxoplasmosis, its timely and accurate diagnosis has a major impact on disease-fighting strategies. T. gondii surface antigen 1 (SAG1), an immunodominant-specific antigen, is often used as a diagnostic tool. Therefore, the aim of this study was the optimization of novel fluorescein isothiocyanate (FITC) labeling of the SAG1-specific IgY antibody to show the potential for immunofluorescence imaging of T. gondii in vitro. The specificity of IgY antibodies was controlled by an enzyme-linked immunosorbent assay (ELISA), and the concentration of the IgY antibody was detected using a spectrophotometer. The optimum incubation time and FITC concentration were determined with a fluorescence spectrometer. The obtained FITC-labeled IgY was used for marking T. gondii tachyzoites, which were cultured in vitro and viewed using light microscopy. The interaction of the fluorescence-labeled antibody and the T. gondii tachyzoites was examined with a fluorescence microscope. In this study, for the first time, a FITC-labeled anti-SAG1 IgY antibody was developed according to ELISA, fluorescence spectrometer, and fluorescence imaging of cell culture. In the future, the obtained FITC-labeled T. gondii tachyzoites' specific IgY antibodies may be used as diagnostic tools for the detection of T. gondii infections in different samples.
Keywords: INFECTION; DIAGNOSIS; PROTEINS; Science & Technology - Other Topics